2010
DOI: 10.1007/s12031-010-9373-6
|View full text |Cite
|
Sign up to set email alerts
|

Association Analysis Between 12 Genetic Variants of Ten Genes and Personality Traits in a Young Chinese Han Population

Abstract: Some genes involved in neurotransmission synthesis and transmission have been hypothesized to affect personality traits. To investigate the possible roles of these genes in personality traits of 16 Personality Factor Questionnaire, we performed a population-based study in a young Chinese Han cohort. In the study, we selected some functional variations in ten candidate genes (COMT, DBH, DRD(2), DRD(3), DAT, MAOA, GRM(1), GRIN2B, 5-TH(2A), and 5-TH(6)) encoding components in dopamine, glutamate, and 5-hydroxytry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 41 publications
2
8
0
Order By: Relevance
“…The allele frequencies of COMT and TPH2 in this study (COMT Met allele: 25.0%; TPH2 G allele: 47.3%) were similar to those in other Asian populations (Chen et al, 2011, Gong et al, 2010, Kim et al, 2009, Lin et al, 2007, Zhang et al, 2011 but different from Caucasian populations (COMT Met allele: 52.0%; TPH2 G allele: 71.3%) (Drabant et al, 2006, Osinsky et al, 2009. The allele frequency of COMT was in accordance with Hardy-Weinberg Equilibrium (P = 0.870), but not for TPH2 (P = 0.015).…”
Section: Clinical Characteristics and Genotypessupporting
confidence: 86%
“…The allele frequencies of COMT and TPH2 in this study (COMT Met allele: 25.0%; TPH2 G allele: 47.3%) were similar to those in other Asian populations (Chen et al, 2011, Gong et al, 2010, Kim et al, 2009, Lin et al, 2007, Zhang et al, 2011 but different from Caucasian populations (COMT Met allele: 52.0%; TPH2 G allele: 71.3%) (Drabant et al, 2006, Osinsky et al, 2009. The allele frequency of COMT was in accordance with Hardy-Weinberg Equilibrium (P = 0.870), but not for TPH2 (P = 0.015).…”
Section: Clinical Characteristics and Genotypessupporting
confidence: 86%
“…These motivated researchers to search for genes for personality traits. Till now, several candidate genes/loci may be associated with personality traits, including COMT, CPY, DA, DARPP-32, DRD2, DRD3, DRD4, 5-HT, 5-HTTLPR, FYN, HTR2A, MAOA, SERT, TH, and TPH (Benjamin et al 2002;Reif and Lesch 2003;Savitz and Ramesar 2004;Ebstein 2006;Heck et al 2009;Gong et al 2010;Li et al 2011a, b).…”
Section: Introductionmentioning
confidence: 99%
“…The gene has been considered as one of the antipsychotic drugs targets. Some studies have demonstrated that the gene is associated with schizophrenia, Alzheimer's disease and personality traits [7][8][9] . Recently, direct genetic analyses have identified some functional variants in the gene.…”
mentioning
confidence: 99%